2007
DOI: 10.1007/s10151-007-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of transperineal ultrasonography in the assessment of the internal opening of cryptogenic anal fistula

Abstract: TPUS and E-TPUS are superior to physical examination in the identification of internal openings in anal fistulas. Hydrogen peroxide injection does not provide additional advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…In particular, a recent systematic review has shown that MRI has similar high sensitivities and better specificity than endoanal US in detecting fistulae, but their specificity values are considered to be diagnostically poor. 18,20,26 The use of ultrasonographic intravenous contrast agents could improve the visualization of the wall of fistulae and abscesses enhancing their vascular tissue and the characterization of perianal abscesses. 23,24 This should be taken into consideration in patients affected by perianal CD, where the exclusion of abscess collections is imperative before the administration of an anti-tumor necrosis factor (TNF) therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a recent systematic review has shown that MRI has similar high sensitivities and better specificity than endoanal US in detecting fistulae, but their specificity values are considered to be diagnostically poor. 18,20,26 The use of ultrasonographic intravenous contrast agents could improve the visualization of the wall of fistulae and abscesses enhancing their vascular tissue and the characterization of perianal abscesses. 23,24 This should be taken into consideration in patients affected by perianal CD, where the exclusion of abscess collections is imperative before the administration of an anti-tumor necrosis factor (TNF) therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the continuous improvement in preoperative imaging [2,3], the reported recurrence rates vary from 8 to as high as 40% [4]. Recurrent fistula-in-ano carries a significant morbidity affecting the quality of life (QOL) due to the disease as well as due to repeated operations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal endosonography, used to visualize the perianal area and especially the perineum, is an alternative when rectal endosonography is not possible because the anus is asymmetrical, causing air artifacts, extreme anal stenosis, or pain[29]. TPUS is also used to image the perianal area in patients with perianal fistula[30,31] or imperforate anus[31]. However, results using EUS seem somewhat better[32,33].…”
Section: Discussionmentioning
confidence: 99%